2013
DOI: 10.1071/sh12135
|View full text |Cite
|
Sign up to set email alerts
|

The high burden of cervical cancer in Fiji, 2004–07

Abstract: The incidence and mortality related to cervical cancer in Fiji is high, whereas Pap smear coverage is very low. Greater investment in alternative screening strategies and preventive measures should be integrated into a comprehensive, strategic cervical cancer control program in Fiji.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(39 reference statements)
0
8
1
Order By: Relevance
“…Only few other studies from the region have assessed coverage of cervical cancer screening, and with the exception of Guam, these studies confirm low coverage of cervical cancer screening in the Pacific Region (Mishra et al, 2001; Balajadia et al, 2008; McAdam et al, 2010; Aruhuri et al, 2012; Hernandez et al, 2013; Law et al, 2013). A recent study from the US Affiliated Guam, American Samoa, Northern Mariana Islands, Federated States of Micronesia and Marshall Islands) examined the practices, attitudes and knowledge of health care workers on cervical cancer screening (Townsend et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Only few other studies from the region have assessed coverage of cervical cancer screening, and with the exception of Guam, these studies confirm low coverage of cervical cancer screening in the Pacific Region (Mishra et al, 2001; Balajadia et al, 2008; McAdam et al, 2010; Aruhuri et al, 2012; Hernandez et al, 2013; Law et al, 2013). A recent study from the US Affiliated Guam, American Samoa, Northern Mariana Islands, Federated States of Micronesia and Marshall Islands) examined the practices, attitudes and knowledge of health care workers on cervical cancer screening (Townsend et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
“…New Caledonia reported not having a fully functioning monitoring mechanism but estimated coverage at 50–60%. Fiji reported to have no monitoring mechanism in place, but 8% coverage has been reported elsewhere (Law et al, 2013). The remaining 7 countries reported screening coverage rates of 4–39% among eligible women.…”
Section: Resultsmentioning
confidence: 99%
“…The age-standardized incidence and mortality per 100,000 per year was 34.7 (95% CI: 31.0-38.5) and 33.9 (95% CI: 29.4-38.3) among ethnic Fijian women respectively, and 24.0 (95% CI: 20.4-27.6) and 13.0 (95% CI: 10.0-16.1) among ethnic Indian women, respectively (Kuehn et al, 2012). Two other studies from Fiji found similar, significant differences between ethic Fijian and ethnic Indian women living in Fiji (Law et al, 2013;Vodonaivalu and Bullen, 2013). Differences in cervical cancer incidence was also reported between ethnic Melanesian (35.8/100,000) and ethnic Europeans (20.4/100,000) in New Caledonia (Parkin et al, 2008).…”
Section: Resultsmentioning
confidence: 80%
“…However, in three studies from Fiji the country specific incidence estimates were lower than the IARC estimate (Parkin et al, 2008;Kuehn et al, 2012;Law et al, 2013). The lower incidence estimates in two of the studies from Fiji (Kuehn et al, 2012;Law et al, 2013) (Parkin et al, 2008(Parkin et al, ) 20.9 18.7 (2002 (Parkin et al, 2008(Parkin et al, ) 50.7 (2002 (Foliaki et al, 2011) 23.9 (2003-09) (Kuehn et al, 2012(Kuehn et al, ) 27.6 (2003 (Kuehn et al, 2012) 20.8 (2004-07) (Law et al, 2013(Law et al, ) 29.7 (2004 (Law et al, 2013) Papua New Guinea 34.5 40.4 (2002) (Parkin et al, 2008) 21. been due to that these studies included the time frame of 2005 and 2006 with probable substantial under-reporting to the national registries, due to a military coup and general turmoil in the country. An alternative explanation for the lower incidence rate found by these two studies from Fiji could be that the studies using hospital based data had improved ability to identify double reported cases.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation